EMPOWERING TEENAGERS AWARE OF NUTRITIONAL STATUS AS AN EFFORT TO PREVENT STUNTING - Sulistyowati, Agus; Kusbandiyah, Jiarti; Rahmawati, Wenny; Annisa, Faida (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Indonesia is a developing country that has quite high nutritional problems. Efforts to improve nutritional status must begin as early as possible, precisely starting from the fetal life period. This period is the early period of life when you are still in the womb until the first 2 years of life. The focus of handling nutritional problems is to prevent malnutrition which is a major health problem in toddlers because it can hinder the growth and development process during the First 1000 Days of Life. There is a need for knowledge regarding stunting in teenagers because teenage girls will face the pregnancy period which is important in preventing stunting. This counseling was carried out in Srigonco Village, Malang Regency. The target of this community service is all junior high school students from grade 7 to grade 9. Prior to carrying out extension activities, there is a process of preparing activities for approximately four weeks prior to implementation activities, starting from determining the type of extension to applying for permits to related parties. As a form of evaluation, the activity was attended by 35 students from grade 7 to grade 9, the participants took part in the activity with very enthusiasm, and the counseling activities ran smoothly.